A Myrmecophylous Mite Myrmozercon tauricus sp. n. of the family Laelapidae (Acari, Mesostigmata) from Ukraine - Trach, V.A.; Khaustov, A.A. (Вестник зоологии, 2011)
A laelapid mite Myrmozercon tauricus Trach et Khaustov, sp. n. collected from nests of ants Crematogaster schmidti (Mayr, 1853) (Hymenoptera: Formicidae) in Crimea (Ukraine) is described. The genus Myrmozercon Berlese, 1902 is recorded in Ukraine for the first time. Из муравейников Crematogaster schmidti (Mayr, 1853) (Hymenoptera: Formicidae) с территории Крыма (Украина) описан новый вид клещей семейства Laelapidae Myrmozercon tauricus Trach et Khaustov, sp. n. Род Myrmozercon Berlese, 1902 впервые приводится для фауны Украины.